Role of the Hepatitis C Virus Core+1 Open Reading Frame and Core cis-Acting RNA Elements in Viral RNA Translation and Replication - Vassilaki, Niki (American Society for Microbiology (ASM), 2008)
Four conserved RNA stem-loop structures designated SL47, SL87, SL248, and SL443 have been predicted in the hepatitis C virus (HCV) core encoding region. Moreover, alternative translation products have been detected from a reading frame overlapping the core gene (core+1/ARFP/F). To study the importance of the core+1 frame and core-RNA structures for HCV replication in cell culture and in vivo, a panel of core gene silent mutations predicted to abolish core+1 translation and affecting core-RNA stem-loops were introduced into infectious-HCV genomes of the isolate JFH1. A mutation disrupting translation of all known forms of core+1 and affecting SL248 did not alter virus production in Huh7 cells and in mice xenografted with human liver tissue. However, a combination of mutations affecting core+1 at multiple codons and at the same time, SL47, SL87, and SL248, delayed RNA replication kinetics and substantially reduced virus titers. The in vivo infectivity of this mutant was impaired, and in virus genomes recovered from inoculated mice, SL87 was restored by reversion and pseudoreversion. Mutations disrupting the integrity of this stem-loop, as well as that of SL47, were detrimental for virus viability, whereas mutations disrupting SL248 and SL443 had no effect. This phenotype was not due to impaired RNA stability but to reduced RNA translation. Thus, SL47 and SL87 are important RNA elements contributing to HCV genome translation and robust replication in cell culture and in vivo.